My double unveiled : the dissipative quantum model of brain - Vitiello, Giuseppe (Advances in consciousness research ;, 2001)
This introduction to the dissipative quantum model of brain and to its possible implications for consciousness studies is addressed to a broad interdisciplinary audience. Memory and consciousness are approached from the physicist point of view focusing on the basic observation that the brain is an open system continuously interacting with its environment. The unavoidable dissipative character of the brain functioning turns out to be the root of the brain's large memory capacity and of other memory features such as memory association, memory confusion, duration of memory. The openness of th.